2017
DOI: 10.1080/19336950.2017.1279370
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive ion channel Piezo2 is inhibited by D-GsMTx4

Abstract: Enterochromaffin () cells are the primary mechanosensors of the gastrointestinal (GI) epithelium. In response to mechanical stimuli cells release serotonin (5-hydroxytryptamine; 5-HT). The molecular details of cell mechanosensitivity are poorly understood. Recently, our group found that human and mouse cells express the mechanosensitive ion channel Piezo2. The mechanosensitive currents in a human cell model QGP-1 were blocked by the mechanosensitive channel blocker D-GsMTx4. In the present study we aimed to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 44 publications
2
51
0
Order By: Relevance
“…3 D ). The NeuroD1 + cell mechanosensitive current biophysical properties were consistent with Piezo2 ( 13 , 23 , 24 ). We attempted to make a NeuroD1 + cell-specific Piezo2 knockout but NeuroD1-cre ; Piezo2 f/f mating resulted in a lethal phenotype ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…3 D ). The NeuroD1 + cell mechanosensitive current biophysical properties were consistent with Piezo2 ( 13 , 23 , 24 ). We attempted to make a NeuroD1 + cell-specific Piezo2 knockout but NeuroD1-cre ; Piezo2 f/f mating resulted in a lethal phenotype ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 57%
“…Therefore, we used pharmacological inhibitors and Piezo2 knockdown to test whether the NeuroD1 + cell mechanosensitive currents are Piezo2. In voltage-clamped primary NeuroD1 + cells stimulated by membrane displacement, we found that mechanosensitive currents were inhibited by Gd 3+ , an established mechanosensitive ion channel blocker ( 23 , 26 ) and D-GsMTx4, a Piezo1 ( 27 ) and Piezo2 ( 24 ) blocker ( Fig. 3 E and F ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…) and piezo 2 (Alcaino et al. ) channels but not the potassium selective mechanically activated channel TREK‐1 (Bae et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, GsMTx4, a relatively selective antagonist for mechano-gated piezo channels (2,6), reduced the pressor and renal sympathetic nerve responses during dynamic hindlimb muscle contraction to a greater extent in "ligated" versus "freely perfused" rats (12). Femoral artery ligation did not, however, increase piezo1 or piezo2 channel protein expression in L 4 and L 5 dorsal root ganglia (DRG) tissue which suggested that an acute and/or chronic sensitization of mechanoreceptors accounted for the exaggerated mechanicallysensitive component of the exercise pressor reflex rather than increased mechanoreceptor expression.…”
Section: Chapter 1 -Introductionmentioning
confidence: 99%